1994
DOI: 10.1103/physrevlett.72.1986
|View full text |Cite
|
Sign up to set email alerts
|

Momentum transfer dependence of nuclear transparency from the quasielasticC12(e,ep) reaction

Abstract: The cross section for quasielastic 12C(e, e'p) scattering has been measured at momentum transfer Q~ = 1, 3, 5 , and 6.8 (Gev/c) ' [I] have suggested that, at sufficiently high momentum transfer, the final (and initial) state interactions of hadrons with the nuclear medium should be reduced, leading to the phenomenon termed "color transparency." Although the arguments were originally formulated within the context of perturbative QCD (high momentum transfer approximation of the strong interaction), recent work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
123
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 15 publications
7
123
2
Order By: Relevance
“…[254] and [255] will further clarify the validity of the present analysis. It is already encouraging to note that the damping employed in the calculations is adequate to describe the observed absorption in the NE18 experiment [267] as discussed in Ref. [258].…”
Section: Extraction Of Spectroscopic Information Frommentioning
confidence: 91%
“…[254] and [255] will further clarify the validity of the present analysis. It is already encouraging to note that the damping employed in the calculations is adequate to describe the observed absorption in the NE18 experiment [267] as discussed in Ref. [258].…”
Section: Extraction Of Spectroscopic Information Frommentioning
confidence: 91%
“…Early calculations based upon the Glauber approximation with energy-independent nucleon-nucleon cross sections and various models of the hadron formation length for point-like configurations predicted substantial enhancement of nuclear transparency for the A(e, e ′ p) reaction at high Q 2 [18][19][20][21]. Nuclear transparency data using the A(e, e ′ p) reaction for 1.0 ≤ Q 2 ≤ 6.8 (GeV/c) 2 have recently been obtained at SLAC by the NE18 collaboration [22,23], but no definitive signal for CT was discerned [24]. On the other hand, the data were limited by statistics and new data of much better accuracy are expected from CEBAF soon, although the maximum Q 2 will be smaller.…”
Section: Introductionmentioning
confidence: 97%
“…For low energies we also consider several traditional nonrelativistic optical models. The calculations are compared with the MIT data [10,11] and with the low-energy data from SLAC experiment NE18 [22,23]. The model is presented in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…The factor exp(−p I · R) is due to the incoming proton wave being properly normalized to 1, where R is a constant vector whose modulus gives the nuclear radius. A reasonable value for p I can be estimated by reproducing, among other things, the NE18 data [28] for the 12 C(e, e ′ p) reaction where the flux of the outgoing proton with p = 1.4 GeV/c is overall reduced by 40%, including the Q 2 behaviour of the related transparency coefficient [36]. It turns out that p I ≪ p, for the above NE18 kinematics typically p I ∼ 50 MeV/c.…”
Section: Spin-independent Nuclear Dampingmentioning
confidence: 99%
“…In fact, the same problem occurs in the semi-inclusive quasi-elastic electroproduction of protons on nuclei about the Final-State Interactions (FSI) of the proton travelling inside the residual nuclear medium after the hard event of virtual photon absorption. The NE18 experiment [28] about the 12 C(e, e ′ p)X reaction has shown that, at 10 GeV energies, the ejectiles interact with the nuclear medium exactly as "normal" protons, before emerging and being actually detected as protons.…”
Section: Spin-independent Nuclear Dampingmentioning
confidence: 99%